Macrotrabecular‐massive hepatocellular carcinoma: A distinctive histological subtype with clinical relevance. Issue 1 (9th May 2018) - Ziol, Marianne; Poté, Nicolas; Amaddeo, Giuliana; Laurent, Alexis; Nault, Jean‐Charles; Oberti, Frédéric; Costentin, Charlotte; Michalak, Sophie; Bouattour, Mohamed; Francoz, Claire; Pageaux, Georges Philippe; Ramos, Jeanne; et al.
Abstract : We recently identified a histological subtype of hepatocellular carcinoma (HCC), designated as "macrotrabecular‐massive" (MTM‐HCC) and associated with specific molecular features. In order to assess the clinical relevance of this variant, we investigated its prognostic value in two large series of patients with HCC treated by either surgical resection or radiofrequency ablation (RFA). We retrospectively included 237 HCC surgical samples and 284 HCC liver biopsies from patients treated by surgical resection and RFA, respectively. Histological slides were reviewed by pathologists specialized in liver disease, and the MTM‐HCC subtype was defined by the presence of a predominant (>50%) macrotrabecular architecture (more than six cells thick). The main clinical and biological features were recorded at baseline. Clinical endpoints were early and overall recurrence. The MTM‐HCC subtype was identified in 12% of the whole cohort (16% of surgically resected samples, 8.5% of liver biopsy samples). It was associated at baseline with known poor prognostic factors (tumor size, alpha‐fetoprotein level, satellite nodules, and vascular invasion). Multivariate analysis showed that MTM‐HCC subtype was an independent predictor of early and overall recurrence (surgical series: hazard ratio, 3.03; 95% confidence interval, 1.38‐6.65; P = 0.006; and 2.76; 1.63‐4.67; P < 0.001; RFA series: 2.37; 1.36‐4.13; P = 0.002; and 2.19; 1.35‐3.54; P = 0.001, respectively). Its prognostic value was retained even after patient stratification according to common clinical, biological, and pathological features of aggressiveness. No other baseline parameter was independently associated with recurrence in the RFA series. Conclusion: The MTM‐HCC subtype, reliably observed in 12% of patients eligible for curative treatment, represents an aggressive form of HCC that may require more specific therapeutic strategies. (Hepatology 2018;68:103‐112).